The terra-cotta dog - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2002)
Stumbling on a fifty-year-old mystery involving a pair of lovers whose bodies are found in a mountain cave beside a dog statue, Inspector Salvo Montalbano investigates the island's past and traces a family's secret back to World War II.